2021
DOI: 10.1001/jamanetworkopen.2020.31266
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Reactogenicity, and Health-Related Quality of Life After Trivalent Adjuvanted vs Trivalent High-Dose Inactivated Influenza Vaccines in Older Adults

Abstract: IMPORTANCETrivalent adjuvanted inactivated influenza vaccine (aIIV3) and trivalent high-dose inactivated influenza vaccine (HD-IIV3) are US-licensed for adults aged 65 years and older. Data are needed on the comparative safety, reactogenicity, and health-related quality of life (HRQOL) effects of these vaccines. OBJECTIVE To compare safety, reactogenicity, and changes in HRQOL scores after aIIV3 vs HD-IIV3. DESIGN, SETTING, AND PARTICIPANTS This randomized blinded clinical trial was a multicenter US study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…We have demonstrated that most people in a UK population cohort receiving ChAdOx1 and BNT162b2 vaccines reported no AEs after vaccination. Indeed, reactogenicity-type symptoms are comparable to those associated with seasonal influenza vaccination 19. Furthermore, 43.7% of follow-up records submitted reported improved overall health and well-being after vaccination.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We have demonstrated that most people in a UK population cohort receiving ChAdOx1 and BNT162b2 vaccines reported no AEs after vaccination. Indeed, reactogenicity-type symptoms are comparable to those associated with seasonal influenza vaccination 19. Furthermore, 43.7% of follow-up records submitted reported improved overall health and well-being after vaccination.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, reactogenicity-type symptoms are comparable to those associated with seasonal influenza vaccination. 19 Furthermore, 43.7% of follow-up records submitted reported improved overall health and well-being after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The first licensure can be obtained by showing non-inferiority versus a “standard” vaccine; then, any data to show superiority, usually involving effectiveness, can be obtained during post-licensure studies. This approach has also been adopted by other manufacturers, such as Sanofi for their high-dose vaccine for older adults, with a relative efficacy trial performed post-licensure 37 , and Novavax, with their matrix-M adjuvanted vaccine 38 .…”
Section: Introductionmentioning
confidence: 99%
“…One postlicensure randomized clinical trial in the United States evaluated the comparative safety of aIIV3 compared with HD-IIV3 in 757 adults aged ≥65 years (378 who received aIIV3 versus 379 who received HD-IIV3) ( 91 ). For the primary outcome, the proportion of participants who reported moderate to severe injection site pain that limited or prevented activity after aIIV3 (12 participants [3.2%]) was noninferior compared with the proportion reporting this outcome following HD-IIV3 (22 participants [5.8%]).…”
Section: Recommendations For the Use Of Influenza Vaccines 2021–22mentioning
confidence: 99%